Ksieni Teresa Chreptowiczówna i emancypacja. Zapis nietrafnej, chociaż metodologicznie pożytecznej hipotezy badawczej - Obremski, Krzysztof (Litteraria Copernicana, 2008)
Founded by St. Bridget the Sacred Saviour Order was not – as e.g. Franciscans and Franciscan Sisters – a „double” order but „dual” one: the Brigittin Monks were subordinated to an abbess. The capitulary teachings preached by Teresa Chreptowiczówna in the middle of the eighteenth century were the speeches (that is the masculine kind of an utterance), what is more, the abbess spoke to the sisters „Your Love” (that is the noble formula). Thus, can we talk about the emancipation in the walls of Hrodna nunnery? A negative answer comes of that: 1. the form „Your Love” describes also the persons of the ignoble origin, 2. in reply to my letter sister Małgorzata Borkowska OSB explained what I could not find in published sources till now: in convents „Your Love” was the form in which the sisters of the ignoble origin were addressed, too.